Fish Identification Across Merbok Estuary Through Dna Barcoding And Environmental Dna (Edna) Metabarcoding In Tropical Mangrove Estuary - Zainal Abidin, Danial Hariz (2022)
Biodiversity hotspots often face a taxonomic information gap, especially those biotas found in tropical mangrove estuarine ecosystems. These megadiverse ecosystems are currently among the most threatened ecosystems in the world due to high human pressures. Moreover, knowledge of the taxonomy and distribution of species in this ecosystem is still incomplete for many groups, especially fish taxa, which hinders the implementation of sustainable biodiversity conservation plans. To fill the taxonomic gap in this species-rich region, this work investigated the diversity of fish communities in a tropical mangrove estuary - the Merbok Estuary in northwestern Peninsular Malaysia using conventional and DNA-based methods. The conventional assessment of ichthyodiversity in the Merbok Estuary and adjacent marine waters recorded a total of 138 fish species from two classes, 18 orders, 47 families, and 94 genera. A repository of specimens was established at the Biodiversity Reference Laboratory, USM, to enable further comparative studies. Subsequently, DNA barcoding based on the COI gene was used to genetically assess the fish diversity in the Merbok Estuary and complement the earlier morphological results. A DNA barcoding reference library of 350 fish individuals was compiled. Of the 138 species initially identified by morphology, the barcodes of 123 species confirm their validity.